FUNDAMENTACION TEORICA EPISTEMOLOGICA PREDOMINANTE EN LOS DISEÑO DE LOS PROGRAMAS DE ESTUDIO EN EL DEPARTAMENTO DE LENGUAS Y LINGUISTICAS DE LA FACULTAD DE CIENCIAS DE LA EDUCACION DE LA UNIVERSIDAD TECNICA DE BABAHOYO Y SU INCIDENCIA, EN LA CALIDAD DE SUS EGRESADOS. - ISABEL CHERREZ CANO (2005)
PREDOMINANT THEORETICAL EPISTEMOLOGICAL FOUNDATION IN THE DESIGN OF THE STUDY PROGRAMS IN THE DEPARTMENT OF LANGUAGES AND LINGUISTICS OF THE FACULTY OF EDUCATIONAL SCIENCES OF THE TECHNICAL UNIVERSITY OF BABAHOYO AND ITS IMPACT ON THE QUALITY OF ITS GRADUATES.